Psychological flexibility is associated with less diabetes distress and lower glycated haemoglobin in adults with type 1 diabetes. Issue 6 (31st May 2022) - Nicholas, Jennifer A.; Yeap, Bu B.; Cross, Donna; Burkhardt, Melanie S.
Abstract: Background: Diabetes distress, self‐efficacy and health literacy are associated with diabetes self‐management and health outcomes. Measures of coping styles and their impact on diabetes self‐management and diabetes‐related distress might add value in identifying those at risk of poorer health outcomes. Current evidence of associations between psychological flexibility/inflexibility and diabetes‐related health outcomes is limited. Aims: To measure associations of psychological flexibility, self‐efficacy and health literacy with diabetes distress and glycated haemoglobin (HbA1c) in adults with type 1 diabetes. Methods: We surveyed 105 adults with type 1 diabetes attending a tertiary diabetes outpatient clinic (mean age 27 ± 7.1 years; 53% men; duration of diabetes 12.6 ± 8.5 years; HbA1c 72 ± 22 mmol/mol, 8.7 ± 2.0%; 34% using insulin pumps). We assessed psychological flexibility, self‐efficacy, health literacy and diabetes distress. Regression models explored the relative contributions of different factors to diabetes distress and HbA1c. Results: The majority of health literacy scores were in the low‐risk range. Those with greater psychological flexibility had higher self‐efficacy ( r = 0.34; P < 0.01) and reported less diabetes distress ( r = −0.54; P < 0.001). In multiple regression analyses, psychological flexibility and self‐efficacy accounted for 36% of the variance in distress score ( P < 0.001). Shorter duration of diabetes ( P < 0.001) and greater psychological flexibility ( P < 0.01) correlated with lower HbA1c. A 10‐point (one standard deviation) higher psychological flexibility score corresponded to a 0.5% lower HbA1c. Conclusions: Greater psychological flexibility was associated with less diabetes distress and lower HbA1c. The psychological flexibility construct might inform alternative interventional approaches aiming to improve well‐being and glycaemic control.